Preparation and Characterization of lron(II, III), Cobalt(II, III) and Nickel(II)-Complexes of 2,2-Dipyridyl. - M. AWADALLAH., RAMADAN (Asian Journal of Chemistry, 2010)
The Fe2+, Fe3+, Co2+, Co3+ and Ni2+ dipyridyl complexes have been synthesised. The isolated complexes are soluble in H2O, EtOH, MeOH, DMF and DMSO. The solid complexes are paramagnetic and have magnetic moment values near to the ground state values of the free ions. The magnetic measurements in connection with the electronic spectra were used to elucidate the different electronic geometrical structures of elements and hence the configuration of the coordination polyhedra around the central metal ions of the investigated complexes. The ligand behaves as a bidentate chelating agent in all the complexes and complexation takes place through two coordinate bonds between the two nitrogen atoms of the two pyridine rings and the central metal ion.